Analysis of Public Sector Financial Reports to Assess Local Government Accountability and Performance - Lilis Dwi Darma; Hafsyah Nabila; Fiqri Haikal; Galih Supraja (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze public sector financial reports in order to assess the accountability and performance of local governments. Financial reports are one of the important instruments used to describe the financial position and evaluate the performance of public sector entities. In the context of local government, financial reports are the basis for decision making, both for internal government parties and for external stakeholders such as the community, creditors, investors, and the central government. This study uses a descriptive analysis approach and case studies to explore the functions, objectives, and stakeholders related to public sector financial reports. The results of the study indicate that public sector financial reports not only function as a tool to measure financial performance, but also as a medium to increase transparency and accountability in regional financial management. In addition, public sector financial reports are also an important reference in decision making related to public policy and regional development. Comparison with the private sector shows significant differences in terms of focus, accountability, and supervision of financial reports. This study provides recommendations for improving the public financial accounting and reporting system in order to create more efficient and accountable management at the local government level